Canine Brucellosis: An Update - Santos, Renato L.; Souza, Tayse D.; Mol, Juliana P. S.; Eckstein, Camila; Paíxão, Tatiane A. (Frontiers in Veterinary Science, 2021)
Canine brucellosis is an infectious and zoonotic disease due to Brucella canis infection, which has been reported worldwide, and it is a major public health concern due to de close contact of dogs and humans. In dogs, canine brucellosis manifests as abortion outbreaks, reproductive failure, enlargement of lymph nodes, and occasionally affects the osteoarticular system. In addition, it is not uncommon the occurrence of asymptomatic dogs. In humans, the disease is associated with a febrile syndrome, commonly with nonspecific symptoms including splenomegaly, fatigue, and weakness. Infection of dogs occurs mostly by the oronasal route while in contact with contaminated tissues such as aborted fetuses, semen, urine, and vaginal secretions. In humans, contact with contaminated fluids from infected dogs is an important source for infection, and it is an occupational risk for professionals that handle infected animals or biological samples. The diagnosis in dogs is largely based on serologic methods. However, serologic diagnosis of canine brucellosis remains very challenging due to the low accuracy of the available tests. Molecular diagnostic methods have been increasingly used in the past few years. Treatment of human patients infected with B. canis is a combined antibiotic therapy. Conversely, treatment of infected dogs is associated with a high frequency of relapse, and should be employed only in selected cases. Currently there is no commercially available vaccine for prevention of canine brucellosis. Therefore, development of novel and improved diagnostic methods as well as the development of efficacious and safe vaccination protocols are needed for an effective control of canine brucellosis and its associated zoonotic risk.